Studi Eksperimental Pengaruh Sudut Sudu pada Turbin Pelton terhadap Performa Pembangkit Listrik Tenaga Gelombang Air Mekanisme Piston - Fikri, Ach Dhaka'; Noerpamoengkas, Ardi; Ulum, Miftahul (Rekayasa, 2025)
Renewable energy is energy that comes from natural resources that are continuously available. Renewable energy will replace fossil fuels that will slowly run out, fossil fuels such as oil, gas and coal. Dependence on fossil fuels results in the depletion of reserves of these energy sources. One of them is a hydroelectric power plant using a Pelton turbine. The working principle of a Pelton turbine is to utilize fluid and water power to generate shaft power. The rotation of the turbine shaft will be converted by the generator into electrical power. In this study, an experiment was conducted on a piston mechanism hydroelectric power plant using a Pelton Turbine with 14 blades with variations in blade angles of 0ᵒ, 10ᵒ, and 15ᵒ with a piston mechanism. The research sought was torque, shaft rotation, mechanical power, voltage, voltage power, turbine power and efficiency. The results of this study show the effect of blade angle variations on the torque produced by the Pelton turbine at an angle of 0ᵒ producing the highest rotational torque of 17.66 Nm, while at an angle of 15ᵒ producing a rotational torque of 17.06 Nm, and the power produced by the Pelton turbine at an angle of 15ᵒ producing higher mechanical power and turbine power compared to angles of 0ᵒ and 10ᵒ, namely mechanical power of 1076.724 J/s and turbine power of 83 watts, shaft rotation of 603 Rpm, and turbine efficiency at an angle of 15ᵒ producing a value of 63%.